1997
DOI: 10.1093/ndt/12.4.741
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and sexual dysfunction

Abstract: Male dialysis patients complaining of sexual dysfunction after correction of anaemia with rHuEpo are characterized by higher levels of serum testosterone and SHBG, but not suppression of hyperprolactinaemia or hyperoestrogenism. Male PD subjects receiving rHuEpo also demonstrated increased LH and FSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 0 publications
6
30
1
Order By: Relevance
“…Erythropoietin therapy has been shown to improve sexual function in the male dialysis patients, with a direct effect upon endocrine function, as well as anemia. 14 Erythropoietin therapy was performed on 81% of HD patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Erythropoietin therapy has been shown to improve sexual function in the male dialysis patients, with a direct effect upon endocrine function, as well as anemia. 14 Erythropoietin therapy was performed on 81% of HD patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia may be a contributing factor for ED 29 and use of recombinant human erythropoietin may provide some benefits over sexual functions of the patients with CKD. 30 In the study, group 1 had lower levels of hemoglobin than groups 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of ED was divided into five categories: no ED (scores of [26][27][28][29][30], mild (scores of [22][23][24][25], mild-to-moderate (scores of 17-21), moderate (scores of [11][12][13][14][15][16], and severe (scores of 6-10). 12 Groups were composed as follows: group1: patients with CKD and ED; group 2: patients with CKD without ED; group 3: control patients without CKD or ED.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in dialysis complaining of sexual dysfunction after correction of anemia with rHuEpo were characterized by higher levels of serum testosterone, but not by suppression of hyperprolactinemia or hyperestrogenism (16) . We observed that the median serum prolactin was high in both HD groups with lack of a significant difference between them.…”
Section: Hormonal Profilementioning
confidence: 95%
“…However, this effect of rHuEpo on patients undergoing hemodialysis was not uniformly present (3,16,32) . Plasma concentration of LH was elevated in patients on maintenance hemodialysis, and the increase is thought to result from diminished release of testosterone from Leydig cells and decreased LH renal clearance (18) .…”
Section: Hormonal Profilementioning
confidence: 99%